HEROISM IN RUDYARD KIPLING’S NOVEL THE JUNGLE BOOK - Hartini Selian; Jumino Suhadi; M. Manugeren (Universitas Islam Sumatera Utara (UISU), 2017)
Abstract This study is about heroism in the novel The Jungle Book by Rudyard Kipling. There are three points of discussion under this title: giving protection, defending rights and gratitude. Defending rights is associated with heroic deeds. A hero is a random citizen that rises to an occasion and performs an action of superhero proportions. Gratitude implies thankfulness or an appreciation of benefits conferred together with a desire, when practicable, to return those benefits. Defending rights is tied to human rights which are universally applicable to one and all. These are the significant components of heroism. One of the relevant and outstanding modern theories of heroism applied here is proposed by Gibbon (2009) stating that hero is just an average man who fights to solve a common problem in today’s society. The study is conducted with Descriptive Qualitative Method proposed by Haughman (2009) in which he states that Qualitative research is a form of social inquiry that focuses on the way people interpret and make sense of their experiences and the world in which they live. Kipling leads children down the jungle path into adventures beyond their day to day imagining and along the way he shows the value of ‘doing for yourself', of 'learning who to trust'. The result shows that heroism is highlighted through the major characters and the conclusive points are some of the significant characters such as Mowgli, Father Wolf, Mother Wolf, Hathi, and Bagheera have done heroic deeds. Their heroism is presented in the forms of giving protection, defending rights and gratitude. Keywords: heroism, human rights, gratitude